Can private providers be trusted to run NHS hospitals after Hinchingbrooke?. (20th January 2015) - Collier, Stephen; Scally, Gabriel
Abstract : The private company Circle is withdrawing from managing the NHS's Hinchingbrooke Hospital. Stephen Collier says that all NHS providers are feeling the strain and that independent providers have an important part to play, but Gabriel Scally wonders whether a profit motive is compatible with the NHS's values